TOP MANAGEMENT’S WILL TO SUPPORT SAFETY CULTURE - Kaila, Harbans Lal (International Journal of Research -GRANTHAALAYAH, 2022)
How Do Company Directors Support Safety Culture Excellence is a deep question to explore the goal of incidents-free status? This article presents a qualitative framework on the issues related to the top/site management at large that are responsible for weak safety culture at the corporates as well as sites resulting in incidents and fatalities. Qualitative research in this paper makes a lot of sense in this regard. 204 industry professionals participated in the study to reflect on the top/site management issues and solutions. Almost 80% industry professionals observed a lack of management’s will to support in safety culture, which amounts to a lag in business sustainability. Top managements need guidance about interventions leading to safety culture transformation.